The Study of the English Article System Errors Made by Secondary School Students in the United Arab Emirates - Adway, Amer Emran (2013)
The study aims at investigating the errors made by grade 12 students in the use of definite and indefinite articles in one of the secondary schools for boys in Umm Al Quwain (UAQ) Educational Zone . The English articles system can be troublesome for Arab ESL/EFL learners because Arabic language has only a definite article , but it lacks indefinite article. Whereas English language has both definite article and indefinite article. The study attempted to find out the most frequent errors and suggest the teaching and learning strategies need to be applied to address these challenges. However, it is found that most frequent errors made by the sample of the study are intralingual errors which are caused by the wrong and traditional teaching methods of teaching the article system .Therefore, some pedagogical applications were suggested that could help teachers of English to improve students’ acquisition of the English article system. It is hoped and recommended that the findings of this study will be utilized in preparing drills to help students improve their ability to use the definite and indefinite articles more appropriately.